Fungsi dan Nilai Mantra dalam Ritual Upacara Muncang Kuta Suku Karo - Marlisnawati Br Karo; Alemina Br. Perangin-angin (BASASTRA: JURNAL KAJIAN BAHASA DAN SASTRA INDONESIA, 2024)
This study aims to preserve the customs and culture that exist in the Karo tribe. The focus of the study is to discuss the mantras and values ​​in the Muncang Kuta ritual ceremony in the Karo tribe's customs. This study is based on a true story that occurred in Mbaruai Village, Sibiru-biru, Deli Serdang. The founders of the village of Kuta Mbaruai, namely the Tarigan Tambak clan as the first clan in the village. In the Muncang Kuta ritual ceremony, mantras are used to express the functions and cultural values ​​contained therein. The study was conducted through a literary anthropology approach, covering the following cultural values: the relationship between humans and God, the relationship between humans and nature, the relationship between humans and others, the relationship between humans and society, and the relationship between humans and themselves. This study uses a descriptive qualitative research method to obtain the necessary data. A total of nine mantras were found in this study. The functions of the mantras found include religious, social, spiritual, protection, healing, and inheritance of traditions.